Specyfika branży a wycena rachunkowości rolnej - Iwasieczko, Beata; Bodzianny, Jolanta; Markiewicz-Rudnicka, Dominika (Business Specificity versus Agricultural Accounting Valuation, 2007)
According to the International Accounting Standard the core of agricultural accounting should be biological growth's record, in order to present quantitative and qualitative changing processes of animals and plants. It requires answering the following questions: • how biological assets, their changes (growth, growing old) and emerging (production, procreation) should be defined? • how principles of the property's component evaluation, complied with results of biological growth process, should be defined? • what is specific in profit and loss account of the agriculture activity? The main aim of this article is an attempt to answer the above mentioned questions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1158, s. 60-71